Global governance systems - Buama, Chester Alexis C. (Oakwood, Ontario, Canada Society Publishing, 2018)
As the world reaches its full potential in achieving sustainable development for each country, the importance of global governance system becomes more relevant than it was before. Factors affecting a state such as globalization, migration, trade and capital flows, and climate change make a state more susceptible to policies adopted by other countries. Thus, these factors show the need of global governance system in maintaining the world order. Global governance system also focuses on increased activities in the global market such as resource domains which do not fall within the jurisdiction of a certain country. In order for countries to remain united in achieving economic goals, coordination and collective decision-making are needed for them to have harmonious trade relationship and increase in economic growth. Several policies and standards are also made by various international institutions and international organizations in order to balance the global level of each country. Examples of these are human rights standards which are guided by the human rights commitments of the international community (U.N. 2015), bank and loan policies, and other guidelines observed by each country.According to the United Nations, global governance actually increases the opportunity to address socio-economic issues and even environmental issues in a well-coordinated, coherent and collaborative manner. Moreover, global governance also promotes more efficient and effective accountability in different countries observing it. The advancement of technology is also one of the factors that global governance considers in making policies and decisions for countries. It can be observed that several developing countries are already keeping up with technological changes happening around the world today. Aside from that, leaders all over the world also analyze the benefits and risks of the decisions that they make in order to achieve successful global governance. In fact, the importance and purpose of the global governance system are widely studied by experts to sustain the development of each country. According to the United Nations multilateral forums, coordination, cooperation, coherence, and policy-making are only few of the efforts that leaders make to address the different issues around the world. Furthermore, efforts should also continue to enhance the representation of developing countries in multilateral institutions and other norms and standard setting bodies (U.N. 2015). Despite the seemingly perfect plan of the leaders worldwide to achieve successful global governance system, challenges are inevitable. According to U.N., these problems usually arise from the absence of adequate mechanisms of other countries to regulate the movement of workers between countries, weak protection of the rights of migrants and their families, as well as restricted access to technologies in health and agriculture. Thus, these gaps impede the progress in social development for global governance’s regime in other countries. According to an article written by Boughton and Bradford, in order to deal with the challenges of the world, global governance should be: more democratic than authoritarian, more openly political than bureaucratic, more integrated than specialized, and operate through soft power rather than hard power. They also added that the idea of global governance is to provide a cooperative leadership that brings together national governments, multilateral public agencies, and civil society in order to achieve commonly accepted goals and be united as one in dealing with challenges. The effectiveness of global governance in addressing the global challenges should be inclusive, dynamic, and able to span national and sectoral boundaries and interests (Boughton et al., 2007). Currently, world organizations and agencies have become more focused on evaluating and trying to improve their performance and increasing their strategies in working together with different organizations in order to achieve the common objectives. In global governance system, leadership is actually one of the most important factors in aiming for a successful development for each country. It is defined by Boughton and Bradford as the highest level of public responsibility that is uniquely invested in heads of state which is necessary to provide the strategic guidance required for the effectiveness of different national and international institutions in order to manage properly the multi-sectoral nature of global threats. This book aims to highlight the importance of global governance in different aspects. Topics which are primarily the concern of leaders of different countries and organizations such as crime, policies, standards and other issues affecting a world leader’s responsibility in decision making will be discussed. Theories and ideologies will also give an insight on how the academic field contributes as a tool with regard to the creation of this system. Institutions such as World Bank, International Monetary Fund (IMF), World Health Organization (WHO), and United Nations (UN) will also be further discussed as this book continues to enlighten the readers about global governance and how the world operates nowadays. Different themes will also be tackled to unlock the areas of global governance as it continues to achieve its desire of a better world for the future generation. It also discusses environmental governance and how different governments around the world combat the problem of global warming. Environmental governance supports and promotes better management of the planet by creating a world environment organization that handles all the issues that affect the current situation of global environmental governance and observing how the world views the importance of taking care of the environment.
Introduction to global governance. -- The UN specialized agencies for global governance. -- Context on global governance system. -- Regional views on world governance. -- The future of the global governance system. -- References. -- Index.
Includes bibliographical references and index
Keywords: International cooperation; Globalization